2015
DOI: 10.1007/s00701-015-2452-2
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic navigation-guided surgery in the semi-sitting position for posterior fossa tumours: a safety and feasibility study

Abstract: EM-guided neuronavigation in the semi-sitting position was safe and technically feasible. It enabled fast and accurate referencing without loss of navigation accuracy despite repositioning of the patient. In contrast to conventional opto-electric neuronavigation there were no line of sight problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Thus, the tip of the navigation stylus can be used when metallic devices are temporarily kept away. Hermann et al reported that they used the AxiEM neuronavigation system Medtronic Powered Surgical Solutions, Fort Worth, TX with the electromagnetic navigation, and there was no need to remove the retractor in sites deeper than the craniotomy margin . The susceptibility of this system to the inaccuracies caused by metallic instruments should be subjected to further examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the tip of the navigation stylus can be used when metallic devices are temporarily kept away. Hermann et al reported that they used the AxiEM neuronavigation system Medtronic Powered Surgical Solutions, Fort Worth, TX with the electromagnetic navigation, and there was no need to remove the retractor in sites deeper than the craniotomy margin . The susceptibility of this system to the inaccuracies caused by metallic instruments should be subjected to further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Hermann et al reported that they used the AxiEM neuronavigation system Medtronic Powered Surgical Solutions, Fort Worth, TX with the electromagnetic navigation, and there was no need to remove the retractor in sites deeper than the craniotomy margin. 23 The susceptibility of this system to the inaccuracies caused by metallic instruments should be subjected to further examination. In this study, we used invasive fiducial markers on the temporal bone, forehead, and contralateral mastoid tip.…”
Section: Discussionmentioning
confidence: 99%
“…It obviates the need for sharp head fixation offering a good alternative to optoelectric techniques, there are no line-of-sight problems, the position of the patient can be changed during surgery, and it allows the use of flexible instruments [24,31,33]. While it was shown to be beneficial especially in the placement of ventricular catheters for different indications [23,24,31,33,43,44], its advantages have been demonstrated also for many other neurosurgical procedures [22,25,26,27,34,45,46,47]. Studies on the accuracy of EM navigation have shown that it is comparable to optoelectric navigation ranging between 0.71-3.51 mm [48] and 0.7-4.4 mm [49].…”
Section: Discussionmentioning
confidence: 99%
“…The transmitter coil was fixed to the table at the side where the DRF was attached. Thereafter, registration of data sets for navigation and confirmation of accuracy were performed [26,27,33,34]. The planned entry point was marked on the patient's skin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation